bird species diversity in Glumpang Tiga subdistrict, Pidie district - Thrina Junita; Asiah M.D; Abdullah Abdullah; Khairil Khairil; Devi Syafrianti (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2020)
Research entitled "Bird Species Diversity in Glumpang Tiga District, Pidie District". The purpose of this study was to determine the level of diversity of bird species. The method used is the line transet method (line transect), which is a method of observation by walking slowly continuously and recording all contacts along both sides of the travel path. The parameters used are bird species and bird diversity index in Glumpang Tiga District, Pidie Regency. Data analysis used Shannon Weaver diversity index formula, analyzed descriptively and displayed in tables and graphs. The results of the study there are 25 species of birds from 15 families. The level of diversity of bird species in three habitats in Glumpang Tiga District, Pidie Regency is classified as moderate with diversity index H` = 2.9745. The species that predominate in residential habitats are Passer montanus, in Nectaria jugularis and in Hirundo tahitica forest habitats. Based on the results of research that has been done, it can be concluded that the level of diversity of bird species found in Glumpang Tiga District, Pidie Regency is included in the medium category. Keywords: Bird diversity, species, habitat type. Penelitian berjudul “Keanekaragaman Jenis Burung di Kecamatan Glumpang Tiga, Kabupaten Pidie”. Tujuan penelitian untuk mengetahui tingkat keanekaragaman spesies burung. Metode yang digunakan adalah metode garis transet (line transect) yaitu pengamatan yang dilakukan dengan cara berjalan perlahan terus menerus dan mencatat semua kontak disepanjang kedua sisi jalur perjalanan. Parameter yang digunakan yaitu jenis burung dan indeks keanekaragamananburung di Kecamatan Glumpang Tiga, Kabupaten Pidie. Analisi data digunakan rumus indeks keanekaragaman  Shannon Weaver, dianalisis secara deskriptif dan ditampilkan dalam bentuk tabel dan grafik. Hasil penelitian terdapat 25 spesies burung dari 15 famili. Tingkat keanekaragaman jenis burung yang berada pada tiga habitat di Kecamatan Glumpang Tiga Kabupaten Pidie tergolong sedang dengan indeks keanekaragaman H`= 2,9745. Jenis yang mendominasi pada habitat pemukiman adalah Passer montanus, pada habitat pemukiman Nectaria jugularis dan pada habitat hutan Hirundo tahitica. Berdasarkan hasil penelitian yang telah dilakukan dapat di simpulkan bahwa Tingkat keanekaragaman spesies burung yang terdapat di Kecamatan Glumpang Tiga, Kabupaten Pidie termaksuk dalam katagori sedang.  Kata kunci: Keanekaragaman burung, jenis-jenis, tipe habitat.